Safety of nurse-directed triage intranasal fentanyl protocol for acute pain management in a European pediatric emergency department: A retrospective observational analysis - Romano, F.; Wendelspiess, M.; Mansour, R.; Abplanalp-Marti, O.; Starvaggi, C.; Holzner, F.; Steiner, I.; Keitel, K. (Frontiers in Pediatrics, 2023)
Background: Nurse-directed pain protocols for intranasal fentanyl administration are not widely implemented in European (EU) pediatric emergency departments (PED). Barriers include perceived safety concerns for intranasal (IN) fentanyl. The aim of this study is to describe our experience with nurse-directed triage IN fentanyl protocol with a focus on safety in a tertiary EU PED. Methods: We conducted a retrospective analysis of patient records of children aged 0-16 years who received nurse-directed IN fentanyl between January 2019 and December 2021 at the PED of the University Children’s Hospital of Bern, Switzerland. Extracted data points included demographics, presenting complaint, pain score, IN fentanyl dosage, concomitant pain medication use, and adverse events. Results: A total of 314 patients were identified with age ranging from 9 months to 15 years. The main indication for nurse-directed fentanyl administration was musculoskeletal pain due to trauma (n = 284, 90%). Mild adverse events (vertigo) were reported in 2 patients (0.6%), without a correlation to concomitant pain medication or protocol violation. The only reported severe adverse event of syncope and hypoxia in a 14 years old adolescent occurred in a setting where the institutional nurse-directed protocol was violated. Conclusion: In accordance to previous studies outside of Europe, our data supports that when appropriately used, nurse-directed IN fentanyl is a safe potent opioid analgesic for pediatric acute pain management We strongly encourage the introduction of nurse-directed triage fentanyl protocols Europe-wide in order to improve effective and adequate acute pain management in children.